PENGARUH PENGGUNAAN SABUN PADAT DENGAN EKSTRAK TEH HIJAU (CAMELLIA SINTESIS) DAN LEMON (CITRUS LIMON) UNTUK MENCERAHKAN KULIT - Annisa Damanik, Pebri; Sitompul, Astrid; Wahidah, Siti; Laurentriana Gea, Sesilia; Christina Hutagalung, Gracede (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to: (1) determine the results of using a solid soap containing green tea (Camellia sinensis) and lemon (Citrus limon) extracts for skin brightening; (2) determine the results of using a solid soap containing lemon extract; and (3) identify the difference in the effects of the two soaps on skin brightness. The study was motivated by an initial survey of 50 respondents aged 17–23, which revealed that 82% still used chemically-based soaps, with 76% experiencing side effects such as dryness, irritation, skin sensitivity, and peeling. An experimental method with a pre-test/post-test control group design was employed. The study involved 20 respondents divided into experimental and control groups. Skin brightness levels were measured before and after a four-week treatment period using a skin tone color chart. Additionally, pH, organoleptic, and irritation tests were conducted to assess the quality of the soap formulations. Evaluation results showed a soap pH of 10.50—compliant with the SNI 3532:2021 standard (range: 6–11)—an average organoleptic score of 84% (categorized as "very good"), and no skin irritation. The findings indicated that the experimental group experienced an average increase in skin brightness of 1.7 shades, while the control group saw an increase of 1.4 shades. The 0.3-shade difference in improvement between the two groups indicates a relatively small disparity. Thus, the solid soap containing green tea (Camellia Sinensis) and lemon (Citrus Limon) extracts meets quality and safety standards and contributes to improved skin brightness.